Study of Organizational Culture and Structure for Implementation of Knowledge Managent in Universities of Medical Sciences - J Khansari; M Hasanzadeh; SDJ Ghazi Mir Saedi; H Dargahi; F Azadeh; M Naghipour (Tehran University of Medical Sciences, 2008)
Background and Aim : Creation of knowledge management (KM) and efforts to use it in the university research programs shows the university society activity to enhance intellectual qualities and improve this effectiveness of the universities on the development and advancement in the countries. The objective of present study was to evaluate the status of organizational culture and structure for implantation of KM in the central libraries of the medical science universities in Iran.Materials and Methods:The present work is an applied research and descriptive-analytic study. The survey population consisted of 80 people who were directors or managers of 29 central libraries in medical science universities. Data collection method was used based on the questionnaire. The validity was checked by researchers and reliability Cronbach's alpha (>0.7). The data & information were analyzed with descriptive statistics and independent t-test by SPSS software package ver. 15.Results: The findings showed that the status of "organizational structure" of KM in these libraries was intermediate, whereas "organizational culture" was in the suitable status. Also in the libraries in which decentralization, revision in knowledge sharing process and Internal Network for knowledge sharing is adopted, higher organizational culture as compared with other libraries, and have significant differences in them (p<0.05).Conclusions: The result of present work is a proof for willingness and propensity of the Iranian librarians and their managers in the process of knowledge sharing and utilization of KM is at the proper level. Therefore, the authorities should provide the necessary structures and other complementary backgrounds for the utilization of KM in Iranian university libraries.